Pengaruh Suhu Pengeringan terhadap Karakteristik Kimia, Fisik dan Sensoris Dendeng Ikan Lemuru (Sardinella lemuru) - Sitinjak, Flora Anggreni; Suparthana, I Putu; Indri Hapsari Arihantana, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
Lemuru fish (Sardinella lemuru) is susceptible to spoilage, especially when its abundance is high, requiring processing. One form of processing is to turn it into lemuru fish jerky.Tthe production of lemuru fish jerky still faces challenges in achieving satisfactory product quality due to the varying meat characteristics of different fish types, necessitating diverse drying temperatures. The aim of this research was to investigate the effect of drying temperature on the chemical, physical, and sensory properties of lemuru fish jerky and to obtain the optimal drying temperature for producing jerky with the best quality. The experiment followed a Randomized block design with five treatment levels: 50°C, 55°C, 60°C, 65°C, and 70°C. Drying was carried out until the moisture content reached a maximum of 12%. All treatments were repeated three times, resulting in 15 experimental units. The data were analyzed using analysis of variance, and treatments showing significant effects were further tested using Duncan's Multiple Range Test. The results showed that drying temperature significantly influenced (P<0,05) the moisture content, fat content, protein content, ash content, hardness, water activity (Aw), color values (L, a*, and b*) and sensory characteristics (color, odor, texture, and overall acceptance) of lemuru fish jerky. Drying at 65°C for 7 hours resulted in lemuru fish jerky with the best chemical, physical, and sensory characteristics, including moisture content of 11.51%, fat content of 6,01%, protein content of 49,61%, ash content of 11,04%, insoluble ash content of 0.07%, Aw value of 0.55, hardness value of 69,25 N, L value of 26.50, a* value of 5.00, b* value of 4.87, and preferred sensory properties of color, odor, texture, and overall acceptance by the panelists.